Self-Regulated Learning of Brazilian Students in a Teacher Education Program in Piaui: The Impact of a Self-Regulation Intervention - Arcoverde, Ângela Regina dos Reis; Boruchovitch, Evely; Acee, Taylor W.; Góes, Natália Moraes (Frontiers in Education, 2020)
Research on teacher education has shown that self-regulated learning (SRL) is relevant for improving learning skills of future teachers. Evidence also suggests that teacher education programs would benefit from fostering SRL in their students and teaching them to use SRL as a teaching practice. This dual focus could help students become more successful students and teachers, better prepared to foster SRL in their future classrooms. The objective of the present research was to investigate learning and study strategies and self-efficacy for learning beliefs among undergraduate students enrolled in teacher education programs at a public university in Brazil. Another aim was to design an SRL intervention, in two formats, and examine the effectiveness of each format at strengthening participants’ self-regulatory skills. To achieve these goals, the study was conducted in two phases. In phase 1, 220 participants completed this Learning and Study Strategies Inventory and the Self-efficacy for Learning form. Findings suggested a need for improving future teacher students´ self-regulatory skills and provided a basis for the second phase, whose goal was to examine an intervention program using a quasi-experimental research design with three stages: pretest, intervention, and posttest. Three classes were randomly assigned to three different treatment conditions: Experimental Group I (EGI) received theoretical content about SRL and self-reflective questions (format 1), Experimental Group II (EGII) received theoretical content about SRL only (format 2), and the Control Group (CG) only completed the assessments. Data from the first phase were used as pretest measures for the second phase. The sample for phase 2 of this study was composed of 53 students. EGI had 22 students, EGII 12, and CG 19. Results comparing EG I with EG II showed no statistically significant group x time interactions. However, when compared with CG, EGI showed statistically significant gains over the control group on five outcome measures, whereas EG II showed statistically significant gains over the control group on three of the outcome measures. This suggested benefits to receiving the interventions and that EG I may yield additional benefits over EG II. Theoretical and practical implications for pre-service teachers and teacher education programs are discussed.